Cold war resistance : the international struggle over antibiotics - Landas, Marc, 1972- (Potomac Books, an imprint of the University of Nebraska Press, 2020)
"In "Cold War Resistance, " Marc Landas uncovers the dark history behind the discovery, production, and distribution of antibiotics, and how the Cold War played a role in today's worsening resistance to antibiotics"--